Single-scan multiplane phase retrieval with a radiation of terahertz quantum cascade laser - Chopard, Adrien; Tsiplakova, Elizaveta; Balbekin, Nikolay; Smolyanskaya, Olga; Perraud, Jean-Baptiste; Guillet, Jean-Paul; Petrov, Nikolay V.; Mounaix, Patrick (Applied physics. B, Lasers and optics, 2022)
Terahertz phase retrieval from a set of axially separated diffractive intensity distributions is a promising single-beam computational imaging technique that ensures the obtention of high spatial resolutions and phase wavefronts, but remains restricted by time-consuming data acquisition processes. In this work, we have adopted an approach, relying on the radiation of a quantum cascade laser and the implementation of an express single-scan measurement of intensity distributions through the continuous on-the-go displacement of a high-sensitivity antenna-coupled microbolometer sensor array. In addition to the simplicity of this practical implementation and the minimization of measurement times, such an approach overcomes the problem of preliminary optimal selections of transverse intensity distributions used in the iterative phase retrieval algorithm and guarantees the required data diversity for high-quality wavefront reconstruction.